Age, origin and tectonic implications of Late Carboniferous-Early Permian felsic magmatic rocks from central Inner Mongolia, south-eastern Central Asian Orogenic Belt. Issue 9 (15th May 2022) - Tang, Jianzhou; Cheng, Jian; Zhang, Zhicheng; Xue, Jinzhuang; Liu, Bo; Duan, Tiejun; Zhan, Weijia; Ding, Cong; Wang, Qi; Zhang, Huaihui; Meng, Yunxi
ABSTRACT: Permo-Carboniferous felsic magmatic rocks are widely exposed on the northern half of the south-eastern Central Asian Orogenic Belt. However, their origin and spatiotemporal distribution are unknown. Herein, zircon U-Pb-Hf isotopic data, major and trace element compositions of the whole-rock, and Sr-Nd isotopic data derived for felsic volcanic rocks and granites of the Chaganaobao and Baiyinaobao areas in central Inner Mongolia are combined with the data from previous studies. The integration of these results reveals that the Uliastai Continental Margin, Erenhot-Hegenshan Ophiolite Belt, and Northern Orogenic Belt have coeval magmatic lull or trough at c. 307 Ma, which overlap with the closure timing of the Hegenshan Ocean. The Latest Carboniferous−Early Permian (c. 303−295 Ma) felsic volcanic rocks in the Chaganaobao area of the Uliastai Continental Margin comprise dacite, trachydacite, and rhyolite, while demonstrating positive whole-rock εNd (t) (+2.9 to +4.7) and zircon εHf (t) values (+7.65 to +13.78). Early Permian granites of the Baiyinaobao area located within the Northern Orogenic Belt show positive εHf (t) values (+ 2.70 to +11.33) and low TFe2 O3 + MgO + TiO2 contents. The geochemical composition reveals that those felsic magmatic rocks mainly originate from the partial melting of juvenile crustal components with subordinate input of mantle-derived melts. Those c. 305−275 Ma felsic magmatic rocks from the north of the south-eastern Central Asian Orogenic Belt exhibit affinities of post-collision type granites in geochemical nature. Therefore, the flare-up of the Early Permian magmatism surrounding the Erenhot-Hegenshan Ophiolite Belt could be related to the extension after the final closure of the Hegenshan Ocean.